On the motivations for the dual-use of electronic and traditional cigarettes - Ronayne, D; Sgroi, D (University of Oxford, 2017)
We apply a classical economic categorization of preferences to identify the motivations of dual-users of electronic and traditional cigarettes. The responses of 2,406 U.S. adults (including 413 dual-users) in 2015 were collected using a novel online survey along with a follow-up in 2016 of 143 of these adults (68 dual-users). A sizeable minority of 37% of dual-users reported viewing electronic and conventional cigarettes primarily as complements. Of those who had never smoked or used electronic cigarettes, only 27% thought the complementarity motive would be primary. Dual-user motivations were associated with quit-attempt, cessation methods, gender and age. One year on, there was a positive relationship between the level of complementarity in the dual-user's motives and their change in self-reported cigarette consumption. It is concluded that the application of a canonical economic classification of preferences may reveal important heterogeneities among the dual-user population.